Reformed confessionalism and the Belhar Confession - Bartle, Roy S. (Koers (Potchefstroom, South Africa), 2025)
The Belhar Confession is a modern confession that addresses issues of race, culture and socioeconomics. It originated from the Dutch Reformed Mission Church’s rejection of apartheid theology and has been adopted by other Reformed denominations, in and beyond Africa, alongside the historical Reformed confessions of the Three Forms of Unity and the Westminster Standards. This article examines whether the Belhar Confession can be subscribed without conflict alongside these historical Reformed confessions. Three common positions taken on confessional subscription are outlined: non-, quia and quatenus subscription. Then, the propositional compatibility of Belhar with the historical confessions is analysed, and potential conflicts in ecclesiology, as well as the doctrines of reconciliation and poverty, are identified. These potential conflicts are realised with quia subscription but are avoidable with quatenus subscription. OPSOMMING Die Belydenis van Belhar is ’n moderne belydenisskrif wat kwessies rakende ras, kultuur en sosio-ekonomiese geregtigheid aanroer. Hierdie belydenis het ontstaan uit die Nederduitse Gereformeerde Sendingkerk se verwerping van die apartheidsteologie en is deur verskeie gereformeerde denominasies, binne en buite Afrika, aanvaar, naas die histories gereformeerde belydenisskrifte van die Drie Formuliere van Eenheid en die Westminster Standaarde. Hierdie studie ondersoek of die Belydenis van Belhar sonder konflik saam met die histories gereformeerde belydenisskrifte onderskryf kan word. Drie algemene benaderings tot konfessionele onderskrywing word onderskei: nie-onderskrywing, quia onderskrywing en quatenus onderskrywing. Vervolgens word die proposisionele versoenbaarheid van die Belydenis van Belhar met die historiese belydenisskrifte ontleed, en potensiële konflikpunte rakende ekklesiologie, betreffende die leerstellings oor versoening sowel as armoede, word geïdentifiseer. Hierdie konflikte kom na vore by quia onderskrywing, maar kan vermy word by quatenus onderskrywing.